Musculoskeletal Computed Tomography: How to Add Value When Reporting Adult Upper Limb Trauma. Issue 2 (4th March 2023) - Sivagurunathan, Gayathri; Shirodkar, Kapil; Hegde, Ganesh; Shamshuddin, Sameer; Proctor, Robin; Naqvi, Jawad; Knowles, David; Ali, Imran
Abstract: There is increasing reliance on computed tomography to evaluate fractures and dislocations following routine evaluation with plain radiography, critical in preoperative planning; computed tomography can provide multiplanar reformats and 3-dimensional volume-rendered imaging, providing a better global assessment for the orthopedic surgeon. The radiologist plays a critical role in appropriately reformatting the raw axial images to illustrate best the findings that will help determine further management. In addition, the radiologist must succinctly report the pertinent findings that will have the most significant bearing on treatment, assisting the surgeon in deciding between nonoperative and operative management. The radiologist should also carefully review imaging to look for ancillary findings in the setting of trauma beyond the bones and joints, including the lungs and rib cage when visualized. In this review article, we will systematically describe key features for fractures of the scapula, proximal humerus, distal humerus, radial head and neck, olecranon, coronoid process through a case-based approach, and distal radius. Although there are numerous detailed classification systems for each of these fractures, we aim to focus on the core descriptors that underpin these classification systems. The goal is to provide the radiologist with a checklist of critical structures they must assess and findings that they should mention in their report, emphasizing those descriptors that influence patient management.